Pyramidal structures: The evidence from Poland - Maria Aluchna; Tomasz Kuszewski (South African Journal of Business Management, 2018)
Background: Pyramidal structures are a specific ownership pattern adopted worldwide, which increases the power of controlling shareholder allowing for lower capital investment. Existing studies still fail to explain the reasons for their adoption in companies.Objectives: The goal was to explore pyramidal structures as a newly developing ownership pattern in an emerging market and to identify firm-level characteristics that determine their adoption. Specifically, we tested three alternative rationales – control leverage, venture and governance – which provide competitive arguments to explain the formation of pyramids.Method: Adopting a linear panel model, we examined a sample of 168 non-financial companies listed on the Warsaw Stock Exchange over the period 2010–2014.Results: The adoption of a pyramid was associated with higher ownership concentration and with lower ownership concentration by a shareholder coalition. There was also a positive relationship between the use of a pyramid and company operation within a business group as well as a smaller number of affiliated companies. We identified a positive link between the use of a pyramid and investment by financial investors.Conclusion: Pyramids serve as a tool for expansion of the business group, important in an environment of costly access to external capital because the business group enables the raising of capital and lowers the risk posed to a new firm. This confirmed the venture and governance rationales, whereas we did not find evidence for the control leverage hypothesis. Governance in a pyramid by financial entities discourages investment by portfolio-oriented financial investors.
Keywords: 650